(untitled) (National Administration Journal, 2024)
Conflict management emerges as a viable alternative for addressing underlying causes when differences arise among members of an organization. This paper aims to propose a conciliation model to manage the causes of conflict between learners of Spanish as a second language and Costa Rican teaching staff at a foreign agency, which is responsible for preparing volunteer candidates in cultural, linguistic, and technical aspects for their future job. It is based on the results of previous research that identified the causes of conflict in both groups. The conciliation model with a collaborative approach was chosen, as it seeks to satisfy all the parties involved through a win-win strategy. As a result, a three-stage conciliation model was designed, which includes various in-person and virtual activities tailored to the limited three-month training period offered by the agency. In addition, the model is supported by principles of strategic educational administration, including a cycle of transformation and continuous improvement that begins with the vision and mission of the entity and continues with stages of planning, organizing, evaluating, and providing feedback.